Kewenangan Inheren Mahkamah Konstitusi terhadap Perkara Pengaduan Konstitutional dengan Objek Putusan Pengadilan - Bagas Christofel Aruan; Umbu Rauta (Jurnal Kajian Pembaruan Hukum, 2022)
The authority of the Constitutional Court is often limited only to the judicial review of statutory products, not practice. The method used for this research is normative legal research using a conceptual approach, legislation, and comparisons. This legal research aims to examine the implementation of constitutional complaint schemes in various countries while reviewing the inherent authority of the Constitutional Court in reviewing constitutional complaint cases with the object of court decisions. The results show that the Constitutional Court of the Republic of Korea has many similarities with the Constitutional Court of the Republic of Indonesia; at the same time, the German Constitutional Court gives rights to individuals, communions, and associations to file a constitutional complaint and the United States Supreme Court establishes several criteria for legal standing for parties who make constitutional complaints. Then, the Constitutional Court has the authority to decide on constitutional objections, including court decisions, considering the court's decision is analogous to the law itself. Furthermore, based on constitutionalism, the constitutional complaint is the inherent authority of the Constitutional Court. KEYWORDS: Constitutional Court, Constitutional Complaint, Court Rulings, Inherent Power.